Didactic reinforcement workshops using the (TBLT) methodology for speaking skill development - Torres Mite, Mareika Romina; Gonzaga Sanmartin, Josselyn Lissbeth (Machala: Universidad Técnica de Machala, 2025)
This thesis work was developed as a response to problems observed in a classroom, where a limited oral proficiency in English was identified in the students. With this, it was defined as a general objective to implement a system of didactic workshops with the use of the Task-Based Learning (TBL) methodology for the improvement of oral expression skills in the students of a classroom of a Higher Basic Education Institution.The research adopted a mixed methodological approach, with a pre-experimental design that contemplated the application of a pre-test, the execution of four sequential workshops and a post-test. The workshops were structured in three phases (pre-task, task and post-task) incorporating contextualized activities, visual material and interaction dynamics in simulated communicative situations. It was supported by the contributions of Willis(1996), Ellis(2020), Long(1985) and Brown(2015), who highlight the effectiveness of the TBL approach for the development of real communicative skills in educational contexts.The results obtained in the post-test revealed significant progress in several aspects of oral skills, although the spontaneous use of polite expressions continues to be something to be reinforced. Therefore, it is concluded that the TBL methodology constitutes an effective strategy to promote integral communicative competence, by promoting active, meaningful learning centered on the needs of the students. Therefore, it is recommended to continue its application in a systematic way, complemented with technological resources, permanent feedback strategies and activities that strengthen the sociocultural dimension of the language.
El presente trabajo de tesis se desarrolló como respuesta a problemáticas observadas dentro de un aula de clase, donde se identificó una limitada competencia oral en inglés de los estudiantes. Con esto, se definió como objetivo general implementar un sistema de talleres didácticos con el uso de la metodología de Aprendizaje Basado en Tareas (TBL) para la mejora de la destreza de expresión oral en los estudiantes de un aula de clase de una Institución de Educación Básica Superior. La investigación adoptó un enfoque metodológico mixto, con un diseño preexperimental que contempló la aplicación de un pre-test, la ejecución de cuatro talleres secuenciales y un post-test. Los talleres se estructuraron en tres fases —pre-tarea, tarea y post-tarea— incorporando actividades contextualizadas, material visual y dinámicas de interacción en situaciones comunicativas simuladas. Se sustentó en los aportes de Willis(1996), Ellis(2020), Long(1985) y Brown(2015), quienes destacan la efectividad del enfoque TBL para el desarrollo de habilidades comunicativas reales en contextos educativos.Los resultados obtenidos en el post-test revelaron un avance significativo en varios aspectos de la habilidad oral, aunque el uso espontáneo de expresiones de cortesía continúa siendo algo por reforzar. Por esto, se concluye que la metodología TBL constituye una estrategia eficaz para promover la competencia comunicativa integral, al propiciar un aprendizaje activo, significativo y centrado en las necesidades del estudiante. Por ello, se recomienda continuar su aplicación de manera sistemática, complementada con recursos tecnológicos, estrategias de retroalimentación permanente y actividades que fortalezcan la dimensión sociocultural del idioma.
Keywords: TASK-BASED LEARNING; TBL; ORAL EXPRESSION; DIDACTIC WORKSHOPS; ENGLISH LANGUAGE TEACHING; SPEAKING SKILL